Optimization and efficacy of an autoinoculation device for managing Liriomyza sativae with Beauveria bassiana - Qikai Zhang; Dengjie Wang; Xinghui Liang; Haihong Wang; Baoqian Lyu (Biological Control)
The leafminer Liriomyza sativae Blanchard (Diptera: Agromyzidae) is a significant pest damaging various agricultural and ornamental crops. Control is hindered by its resistance to multiple insecticides. This study aimed to develop and optimize an autoinoculation device specifically for controlling L. sativae and to assess the device’s efficacy in field applications. The initial phase involved screening to identify a strain of Beauveria bassiana (Balsamo-Crivelli) Vuillemin that was highly virulent to L. sativae. After selection of the optimal strain, the attractant formulation was refined and the device design was optimized to maximize pest attraction and infection rates. Short- and long-term field trials were then conducted to evaluate the device’s effectiveness in the control of pest populations. Results showed that the XJWLMQ-1 strain of B. bassiana had the highest rates of spore production, pest infection, and lethality to the targeted leafminer. The most effective attractant was a blend of trans-2-hexenal, cis-3-hexenol, 1-octen-3-ol, cis-3-hexenyl acetate, and α-ionone in a 4:1:1:3:1 ratio at 0.8 g/L concentration. Optimal efficacy was achieved by positioning the attractant 20 cm from the fungal spores and 20 cm above the cowpea canopy. Both short- and long-term trials confirmed that the autoinoculation device was effective in controlling L. sativae populations, suggesting its effective use for biological control of the target pest.